Neuroprotectin D1 Protects Against Postoperative Delirium-Like Behavior in Aged Mice - Zhou, Ying; Wang, Jiayu; Li, Xiaofeng; Li, Ke; Chen, Lei; Zhang, Zongze; Peng, Mian (Frontiers in Aging Neuroscience, 2020)
Postoperative delirium (POD) is the most common postoperative complication affected elderly patients, yet the underlying mechanism is elusive and without effective therapy. Neuroinflammation hypothesis has been emerging as the pathogenesis of POD. Recently, accumulating evidence has supported the role of specialized proresolving lipid mediators (SPMs) in regulating inflammation. Neuroprotectin D1 (NPD1), a novel DHA-derived lipid mediator, has shown its potent immunoresolvent and neuroprotective effect in several disease models associated with inflammation. Here, using a mouse model of POD, we investigated the role of NPD1 in postoperative cognitive impairment by assessing systemic inflammatory changes, permeability of blood-brain barrier (BBB), neuroinflammation, and behavior of aged mice at different time points. We reported that a single dose of NPD1 prophylaxis decreased the expression of TNF-α and IL-6 and upregulated the expression of IL-10 in peripheral blood, hippocampus and prefrontal cortex. Additionally, NPD1 limited the leakage of BBB by increasing the expression of tight junction associated proteins such as ZO-1, claudin-5 and occludin. NPD1 also abolished the activation of microglia and astrocytes in hippocampus and prefrontal cortex , which resulted in improved general and memory function. In addition, NPD1 treatment modulated expression of inflammatory cytokines profile and improved the expression of M2 marker CD206 in LPS-stimulated macrophages, which could partly elaborate the beneficial effects of NPD1 on inflammation. Collectively, these findings verify the proresolving activities of NPD1 in the proinflammatory milieu both in vivo and in vitro, and provide a novel approache to treat POD as well as other neuroinflammation-driven diseases.